Madiun City Government Economic Policy Strategy: Islamic Economic Prespective - Mohamad Nur Efendi; Kusnul Ciptanila Yuni K; Nasrulloh Nasrulloh; Sumawan Sumawan (Islamic Economics Journal, 2023)
News of inflation occurring in various parts of the world has spread, even the President of Indonesia Mr. Joko Widodo mentioned in his speech about the shadow of the world in 2023. The city of Madiun is one of the areas in East Java which is responding to the preparation of strategies to deal with the 2023 crisis. Through a qualitative descriptive method, this article aims to analyze the economic policy strategy of the Madiun city government based on an Islamic economic view. The primary data comes from the speech of the mayor of Madiun at the coordination meeting of local government officials. The findings of this study reveal that the Madiun city government implements a food security strategy from Prophet Yusuf AS and is supported by a price intervention strategy from Ibnu Taimiyah's perspective. The Madiun city government used this strategy to deal with inflation and predictions of a food crisis in 2023.